Quality of Life of Patients with Abdominal Stoma and the Predictor Factors: A Cross-sectional Study in a Teaching Tertiary Hospital - Abdul Wahab, Patimah; Mohamed, Nurhazelin; Ismail, Norsuzana; Shahadan, Siti Zuhaidah; Hassan, Intan Idiana; Haryanto, Haryanto (Malaysian Journal of Medical Sciences, 2026)
Background: An abdominal stoma is instrumental in preserving life; however, its impact on a patient’s quality of life (QoL) is multifaceted and influenced by a complex interplay of various factors, including sociodemographic and clinical factors. This study aimed to assess patients’ QoL and examine its relationship with these factors. Methods: A cross-sectional telephone survey was conducted among patients with abdominal stoma at a teaching tertiary hospital from December 2020 to February 2021. Participants were identified from the medical records of postoperative patients with a stoma and underwent eligibility assessment via medical record reviews. Data on sociodemographic characteristics and clinical conditions were obtained from medical records. A telephone survey employing the City of Hope-Quality of Life-Ostomy Questionnaire (CoH-QoL-OQ) facilitated QoL data collection. Predictor factors of QoL were examined using multiple linear regression. Results: The mean QoL score was 6.86 (standard deviation [SD] = 0.84), indicating a moderate to high QoL. Physical well-being was the most affected (6.29; SD = 0.76), and spiritual well-being was the least affected (8.07; SD = 1.17). Employment status (b = –0.94 [95% CI: –1.67, –0.22]; P = 0.014) and colorectal cancer (CRC) (b = 0.92 [95% CI: 0.13, 1.71]; P = 0.025] were significant predictors of QoL (R² = 0.389). Conclusion: The study found that patients with stomas generally experience a moderate QoL, with poorer QoL associated with unemployment and non-CRC diagnoses. These findings provide valuable insight into the need to strengthen patient-centred care to ensure appropriate and equitable supportive interventions for all patients.